Quantum dots in biomedical applications. (August 2019) - Wagner, Angela M.; Knipe, Jennifer M.; Orive, Gorka; Peppas, Nicholas A.
Graphical abstract: Abstract: Semiconducting nanoparticles, more commonly known as quantum dots, possess unique size and shape dependent optoelectronic properties. In recent years, these unique properties have attracted much attention in the biomedical field to enable real-time tissue imaging (bioimaging), diagnostics, single molecule probes, and drug delivery, among many other areas. The optical properties of quantum dots can be tuned by size and composition, and their high brightness, resistance to photobleaching, multiplexing capacity, and high surface-to-volume ratio make them excellent candidates for intracellular tracking, diagnostics, in vivo imaging, and therapeutic delivery. We discuss recent advances and challenges in the molecular design of quantum dots are discussed, along with applications of quantum dots as drug delivery vehicles, theranostic agents, single molecule probes, and real-time in vivo deep tissue imaging agents. We present a detailed discussion of the biodistribution and toxicity of quantum dots, and highlight recent advances to improve long-term stability in biological buffers, increase quantum yield following bioconjugation, and improve clearance from the body. Last, we present an outlook on future challenges and strategies to further advance translation to clinical application. Statement of Significance: Semiconducting nanoparticles, commonly known as quantum dots, possess unique size and shape dependent electrical and optical properties. In recent years, they have attracted much attention in biomedical imaging to enable diagnostics, single molecule probes, and real-time imaging of tumors. This review discusses recent advances and challenges in the design of quantum dots, and highlights how these strategies can further advance translation to clinical applications.